Calculating with lenses: optimising bidirectional transformations - Pacheco, Hugo (2011)
This paper presents an equational calculus to reason about bidirectional transformations specified in the point-free style. In particular, it focuses on the so-called lenses as a bidirectional idiom, and shows that many standard laws characterising point-free combinators and recursion patterns are also valid in that setting. A key result is that uniqueness also holds for bidirectional folds and unfolds, thus unleashing the power of fusion as a program optimisation technique. A rewriting system for automatic lens optimisation is also presented, to prove the usefulness of the proposed calculus.